Unmanned air vehicle adaptability and application evaluation for new rice panicle fertilizers: Fertilizer characteristics and mechanical adaptability - Shilin Zhu; Wei Zhou; Li Zhu; Boteng Sun; Song Huang; Zhenyuan Wu; Qin Qin; Tao Wang; Yong Chen; Fei Deng; Xiaolong Lei; Youfeng Tao; et al. (Technology in Agronomy, 2022)
High-efficiency fertilizers suitable for mechanical spraying can improve the fertilizer application and utilization efficiency. In this study, two types of granular compound fertilizers suitable for unmanned air vehicle spraying were developed using urea, potassium chloride, humic acid, and an amino acid synergist according to the fertilization requirements of rice at the booting stage. The physical and chemical properties of the compound fertilizers were analyzed by Fourier transform infrared spectroscopy and scanning electron microscopy. The release kinetics of the fertilizer was studied via a soil column leaching experiment. The effect of fertilizer particles on unmanned air vehicle spraying uniformity was studied via an orthogonal simulation experiment. Results showed that the chemical interaction between compound-fertilizer raw materials formed complexes such as C-NH-C and -CO-NH-, which caused a change in fertilizer particle morphology. This led to chemical monolayer adsorption or internal fertilizer diffusion, which in turn delayed the fertilizer release by 5−10 d. A simulation bench test showed that the fertilizer particle hardness and roundness exceeded 20 N and 85%, respectively, while the particle size was in the range of 2.07−5.13 mm, which resulted in good unmanned air vehicle spraying uniformity with a lateral variation coefficient of less than 15%. Finally, the experimental field results demonstrated that the new compound fertilizers, when sprayed by an unmanned air vehicle, could improve the economic benefit by 916−2742 CNY ha−1 without reducing the nitrogen utilization rate and rice yield. The new compound fertilizers exhibit delayed release, good spraying uniformity, and improved economic benefit, rendering them suitable for large-scale promotion and application.